A miniaturized reconfigurable broadband attenuator based on RF MEMS switches. (20th May 2016) - Guo, Xin; Gong, Zhuhao; Zhong, Qi; Liang, Xiaotong; Liu, Zewen
Abstract: Reconfigurable attenuators are widely used in microwave measurement instruments. Development of miniaturized attenuation devices with high precision and broadband performance is required for state-of-the-art applications. In this paper, a compact 3-bit microwave attenuator based on radio frequency micro-electro-mechanical system (RF MEMS) switches and polysilicon attenuation modules is presented. The device comprises 12 ohmic contact MEMS switches, π -type polysilicon resistive attenuation modules and microwave compensate structures. Special attention was paid to the design of the resistive network, compensate structures and system simulation. The device was fabricated using micromachining processes compatible with traditional integrated circuit fabrication processes. The reconfigurable attenuator integrated with RF MEMS switches and resistive attenuation modules was successfully fabricated with dimensions of 2.45  ×  4.34  ×  0.5 mm 3, which is 1/1000th of the size of a conventional step attenuator. The measured RF performance revealed that the attenuator provides 10–70 dB attenuation at 10 dB intervals from 0.1–20 GHz with an accuracy better than  ±1.88 dB at 60 dB and an error of less than 2.22 dB at 10 dB. The return loss of each state of the 3-bit attenuator was better than 11.95 dB (VSWR  <  1.71) over the entire operating band.